Microbiota dynamics preceding bariatric surgery as obesity treatment: a comprehensive review - Zambrano, Ana Karina; Paz-Cruz, Elius; Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Tamayo-Trujillo, Rafael; Guevara-Ramírez, Patricia; Zambrano-Villacres, Raynier; Simancas-Racines, Daniel (Frontiers in Nutrition, 2024)
The review present data on the intricate relationship between bariatric surgery, gut microbiota, and metabolic health in obesity treatment. Bariatric surgery, is recognized as an effective intervention for managing morbid obesity, including various techniques with distinct mechanisms of action, efficacy, and safety profiles including Roux-en-Y Gastric Bypass (RYGB), Sleeve Gastrectomy (SG), Laparoscopic Adjustable Gastric Banding (LAGB), and Biliopancreatic Diversion (BPD). RYGB and SG are the most prevalent procedures globally, inducing gut microbiota changes that influence microbial diversity and abundance. Post-surgery, alterations in bacterial communities occur, such as the increased of Escherichia coli inversely correlated with fat mass and leptin levels. During digestion, microbiota produce physiologically active compounds like bile acids (Bas) and short-chain fatty acids (SCFAs). SCFAs, derived by microbial fermentation, influence appetite, energy metabolism, and obesity-related pathways. Bas, altered by surgery, modulate glucose metabolism and insulin sensitivity. Furthermore, SG and RYGB enhance incretin secretion, particularly glucagon-like peptide 1 (GLP-1). Therefore, understanding microbiota changes after bariatric surgery could be crucial for predicting metabolic outcomes and developing targeted interventions for obesity management.